2012
DOI: 10.1364/ao.51.004916
|View full text |Cite
|
Sign up to set email alerts
|

Overview of anisotropic filtering methods based on partial differential equations for electronic speckle pattern interferometry

Abstract: In this paper, we first present the general description for partial differential equations (PDEs) based image processing methods, including the basic idea, the main advantages and disadvantages, a few representative PDE models, and the derivation of PDE models. Then we review our contributions on PDE-based anisotropic filtering methods for electronic speckle pattern interferometry, including the second-order, fourth-order, and coupled nonoriented PDE filtering models and the second-order and coupled nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is worthy to note that many diffusion models adopt the constant step size [25][26][27][28] for each iteration or whole iterative process of the image. Here a better iteration step is propsoed in the Eq.…”
Section: Denoising Model Based On Adaptive Anisotropic Diffusionmentioning
confidence: 99%
“…It is worthy to note that many diffusion models adopt the constant step size [25][26][27][28] for each iteration or whole iterative process of the image. Here a better iteration step is propsoed in the Eq.…”
Section: Denoising Model Based On Adaptive Anisotropic Diffusionmentioning
confidence: 99%
“…Several different denoising methods have been reported so far to reduce speckle noise in DSPI. [10][11][12][13][14][15][16][17][18][19][20][21][22] Various approaches for speckle noise reduction including gray-scale modification, frame averaging, low-pass filtering, and short space spectral subtraction image restoration technique have been suggested by Lim and Nawab. 10 Another considerable work by Varman and Wykes 11 presents a demonstration of curve fitting and fast Fourier transform techniques to reduce residual speckle noise.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another considerable work by Varman and Wykes 11 presents a demonstration of curve fitting and fast Fourier transform techniques to reduce residual speckle noise. Tang et al 12 gave an overview about the exploitation of partial differential equations (PDEs) and the anisotropic filter-based method for DSPI fringes denoising. Bernini et al 13 exploited bidimensional empirical mode decomposition to reduce speckle in DSPI, which gives high-and low-frequency mode called intrinsic mode functions (IMFs): the technique recommends to remove the first IMF that contain speckle noise and then reconstruct others IMFs to obtain despeckled fringe patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Noise is an inevitable problem in fringe pattern analysis, and fringe patterns with noises must be denoised before further analysis. Current denoising techniques can be generally classified into two groups, spatial domain techniques [15,[59][60][61][62][63][64][65][66][67] and transform domain techniques [19,42,[68][69][70]. The spatial domain techniques reduce noises by a smoothing process.…”
Section: Denoising Techniquesmentioning
confidence: 99%
“…The mean and median filtering methods [15], oriented partial differential equations (OPDE) [59][60][61][62], coherence enhancing diffusion (CED) [63,64] and spin filters [65][66][67] are examples of those spatial domain techniques. A comparison study of the spatial domain techniques can be found in Ref.…”
Section: Denoising Techniquesmentioning
confidence: 99%